THE EFFECTIVENESS OF EDUCATION IN INCREASING HYPERTENSION KNOWLEDGE IN HYPERTENSION PATIENTS AT THE PRATAMA CLINIC UIN SUNAN AMPEL SURABAYA - Asiyah, Siti Nur; Rizqiah, Dhuhrotul; Retnaninggalih, Anjani Putri; Suyatno, Restiani L.; Winarto, Agnestria; Zahroh, Aini Nurul Fatimatuz; Najjah, Alisa Hidayatun; Syaroh, Roza Maulida Muhanna; Purwati, Nur Fatihah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Hypertension is a condition where the systolic blood pressure is 130 mmHg or diastolic is 80 mmHg; 80 – 95% in cases of essential hypertension. Hypertension can also be called the